Introduction of Marketing Strategies for Plastic Waste Recycling Products to Increase the Entrepreneurial Spirit of Madrasah Ibtida'iyah Students - Suparwi; Sri Purwati; Sri Mayasari; Nancy Oktyajati; Bagus Andika Fitroh (Universitas Veteran Bangun Nusantara, 2024)
This community service activity aims to improve the insights and skills of MI Hidayatul Insan Karanganyar students about marketing strategies in plastic waste recycling products. This activity was carried out at MI Hidayatul Insan Karanganyar by involving grade V students with a total of 22 students. The implementation method includes counseling and initial education regarding plastic waste management, reviewing plastic waste recycling activities, introducing marketing strategies, and preparing a marketing plan for brooch products from used straws. The results of this activity reflect an increase in students' understanding of plastic waste management, their ability to recycle, and knowledge of marketing strategies. It is concluded that this service activity provides an initial understanding of entrepreneurship and marketing of plastic recycled products to elementary level students. This activity plays a role in shaping an entrepreneurial mindset among students as well as providing a positive outlook on the practice of recycling plastic waste.